A Quantitative GIS and AHP Based Analysis for Geodiversity Assessment and Mapping - Ferrando, Andrea; Faccini, Francesco; Paliaga, Guido; Coratza, Paola (Sustainability, 2021)
In recent times, the issues of geodiversity assessment and mapping have been subject of great attention, and many evaluation methodologies, either quantitative or qualitative, have been developed. In this research, a first assessment of geodiversity in the Liguria region has been carried out, according to a quantitative method based on spatial analysis techniques implemented in a GIS environment. This method considers four diversity indices obtained by grid analysis, relevant to the four main aspects of geodiversity: geology, geomorphology, hydrogeology and pedology. The geodiversity index was calculated two times, first with a non-weighted sum, then with a weighted sum of the four diversity indices. In the second case, the weights have been assigned according to a semi-quantitative analytical hierarchy process method (AHP) based on experts’ judgment. The results show that the Liguria region is characterized by many areas with high geodiversity, most of them internationally known by geoscientists and tourists for their valuable geoheritage and for their stunning landscapes. The correspondence between these areas and the protected areas of the european Natura 2000 network suggests a link between geodiversity and biodiversity.